Hospital Electronic Medical Record Storage Plan - Heltiani, Nofri; Khairunnisyah; Arifin, Ismail (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
The Electronic Medical Record Storage System aims to increase efficiency at Bhayangkara Bengkulu Hospital. However, based on the initial survey conducted, it was discovered that the medical record storage system was still carried out manually. Borrowed medical records are recorded in the expedition book before being borrowed and distributed by officers so that it takes time to get to the unit concerned. Officers store medical records not according to the shelves based on the patient's medical record number and many medical records are damaged/recorded. This research aims to design an electronic medical record storage system at Bhayangkara Hospital, Bengkulu. This type of research is descriptive qualitative with the waterfall method. The subjects of this research were medical records and IT officers. The research data used is primary data obtained by observation using a checklist sheet, then the data is processed and analyzed univariately. The result of this research is a design for an electronic medical record storage system that is ready to be implemented. Through this implementation, it is hoped that efficiency and accuracy in medical record management can be improved. The suggestions put forward are to make changes to the medical record file storage shelves to make them more orderly, provide training to officers in using the new system, and carry out impact evaluations to measure efficiency and patient satisfaction due to system changes.